Prevalence and associated factors of self-medication among the Bengali Hindu population of north 24 Parganas, West Bengal, India: an ethnographic study - Mondal, Priyabrata; Das, Abhijit; Paul, Suvankar (International Journal Of Community Medicine And Public Health, 2026)
Background: Self-medication is now a global concern, and self-medication is described as medication practices without knowing the doses and duration by individuals’ own concern without any suggestion of a medical practitioner or healer. The main objective of the study is to understand the prevalence and associated factors behind self-medication practice among the Bengali Hindu population of North 24 Parganas. This ethnographic study examines the knowledge, patterns, and implications of self-medication without a doctor. Methods: From this perspective, a cross-sectional ethnographic study has been conducted among the Bengali Hindu population of north 24 Parganas district, West Bengal, India. Through the purposive sampling method, about 327 individuals have been selected as a sample to complete the study. Some ethnographic research tools and techniques, such as intensive interviews, case studies, participant observation, etc., have been used for data collection. Results: The prevalence of self-medication is 57.18% among the studied population. Overall, minor illnesses were the main reason for self-medication (27.27%), followed by previous experience or knowledge (25.13%) and money saving (19.79%). The Bengali Hindu population of this area reveals a complex interplay of Western Bio-medicine (WBM) or modern pharmaceuticals, healthcare access challenges, and socio-cultural norms and beliefs. Conclusions: The prevalence of self-medication is high among the Bengali Hindu population of north 24 Parganas due to easy access to Western bio-medicine and the availability of local medicine shops. Local pharmacists have a great role in the practice of self-medication in the studied area.